The Effectiveness of Legal Arrangements for Domestic Tourists Victims of Discrimination in Tourist Areas - Ni Putu Pebrina; I Gede Agus Kurniawan; Ni Putu Sawitri Nandari; Dewa Krisna Prasada (LUTUR Law Journal, 2025)
Discrimination against domestic tourists in popular tourism areas, such as Canggu in Badung Regency, raises serious concerns regarding consumer protection and social justice. As a state governed by law, Indonesia has established various legal instruments to safeguard the rights of consumers, including tourists, from discriminatory practices. However, challenges arise when the implementation of these regulations does not align with the spirit of legal protection mandated by statutory law. This situation reflects a gap between the normative framework and the practical reality in the field. This research aims to examine the legal position and responsibility of business actors toward domestic tourists who experience discrimination, as well as to assess the effectiveness of Indonesia’s positive law in providing real protection. The study adopts a normative legal research method (doctrinal research) employing both statutory and conceptual approaches. The data are drawn from national legislation, regional regulations, legal doctrines, and relevant scholarly literature. The findings reveal that business actors in the tourism sector bear clear legal responsibilities under the Consumer Protection Act, the Tourism Act, and regional regulations of Bali Province and Badung Regency, which emphasize the principle of non-discrimination. The novelty of this research lies in its in-depth analysis of the effectiveness of local regulations in addressing discrimination against domestic tourists, an issue that has received less attention compared to the protection of international visitors. This study contributes by highlighting the urgency of strengthening implementation, supervision, and accessible complaint mechanisms to ensure that the legal framework operates effectively in protecting domestic tourists.